2022
DOI: 10.1002/ps.6847
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity, horizontal transfer, and physiological and behavioral effects of cycloxaprid against Solenopsis invicta (Hymenoptera: Formicidae)

Abstract: BACKGROUND The red imported fire ant, Solenopsis invicta Buren, is a significant urban, agricultural, and medical pest with a wide distribution in the world. Surface or mound treatment using contact insecticide is one of the main methods to control S. invicta. In the present study, cycloxaprid, a newly discovered neonicotinoid insecticide, was evaluated for S. invicta control and compared with two referent insecticides, imidacloprid and bifenthrin. RESULTS Surfaces or sand treated with cycloxaprid, imidaclopri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Presently, S. invicta control relies predominantly on chemical insecticides, but prolonged use raises environmental and health concerns. 24 While resistance to different insecticides has not been reported, it remains a potential risk. Therefore, there is an urgent need for an effective, eco-friendly alternative to manage S. invicta infestations.…”
Section: ■ Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Presently, S. invicta control relies predominantly on chemical insecticides, but prolonged use raises environmental and health concerns. 24 While resistance to different insecticides has not been reported, it remains a potential risk. Therefore, there is an urgent need for an effective, eco-friendly alternative to manage S. invicta infestations.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Presently, S. invicta control relies predominantly on chemical insecticides, but prolonged use raises environmental and health concerns . While resistance to different insecticides has not been reported, it remains a potential risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, untreated ants carrying and moving corpses killed by certain insecticides may acquire a lethal dose of the toxicants [ 67 , 70 ]. In the case of synthetic pesticides, Zhang et al [ 71 ] reported that a significant horizontal transfer effect was achieved in the first-round transmission (mortality > 65% for 108 h) when recipient ants were mixed with donor ants previously exposed to 10 μg/cm 2 of cycloxaprid or imidacloprid. Similarly, bifenthrin demonstrated significant horizontal activity, with 95% of the recipient ants killed at 20 °C when 20% of the ants were treated (donors–recipients ratio = 1:4), and 60% mortality at 20 °C when 10% were treated (donors–recipients ratio = 1:9), and 30 °C when 20% were treated [ 70 ].…”
Section: Discussionmentioning
confidence: 99%